Life expectancy by ethnic origin in Chile - Sandoval, Moisés H.; Alvear Portaccio, Marcela E.; Albala, Cecilia (Frontiers in Public Health, 2023)
Background Ethnic and racial differences in life expectancy have been well established in different societies. However, even though an important part of the population of Latin America is Indigenous, there is little knowledge about them. Objective Determine if there are ethnic differences in life expectancy at birth and at 60 years in Chile, and if the Mapuche (largest Indigenous ethnic group) have similar life expectancy to other Indigenous peoples. Method Life tables for the Mapuche and other Indigenous groups and non-Indigenous people were built using the 2017 census. Specifically, we used the questions of the number of live children born and the number of surviving children. With this information, using the indirect method of own children we determined infantile mortality. Then, using the relational logit model and the model life table (west), we estimated the survival function for all ages. Results Indigenous Chileans have seven years lower life expectancy at birth than the non-Indigenous population (76.2 vs. 83.2 years). The differential at age 60 is 6 years (20.3 vs. 26.4 years). We also found that Mapuche have an even greater disadvantage in survival than other ethnic groups. This is reflected in 2 years less life expectancy, both at birth and at 60 years. Discussion Our results ratify the existence of marked ethnic-racial inequality in the extension of life in Chile and demonstrate a greater disadvantage in terms of survival of the Mapuche compared to other Indigenous and non-Indigenous groups. It is thus of great relevance to design policies that would decrease the existing inequalities in lifespan.